AB1157 Biological therapy in patients with chronic juvenile idiopathic arthritis-associated uveitis: Results of follow-up in a multidisciplinary unit. (23rd January 2014) - Calvo, I.; Lopez, B.; Marco, A.; Henriquez, S.; Rodriguez, Y.; Aviño, J.; Martinez, R.; Harto, M.
Abstract : Background: Juvenile idiopathic arthritis-associated uveitis causes blindness in the paediatric age group. Between 20-35% of patients are refractory to treatment. Objectives: To evaluate the response to the biological drugs used and to evaluate the changes that have been required to maintain remission. Methods: This is a non-comparative retrospective study of a series of 42 patients with uveitis that is refractory to conventional treatment associated with JIA in which all patients have received biological therapy. The different clinical forms of JIA and ANA status are considered. The ophthalmological and joint controls in order to evaluate disease activity are in accordance with the clinical follow-up protocol in our Unit. The different biological drugs and the changes required will be used in order to maintain remission of the disease. Results: Patients were divided by gender into 26 girls and 16 boys ranging from 3.8-9.2 years of age with a mean age of 10.2 years. Based on the form of JIA, 35.7% (15) were polyarticular, 28.5% (12) were oligoarticular, 7.1% (3) were extended oligoarticular, 14.2% (6) were arthritis-enthesitis, 9.5% (4) were psoriatic and 4.7% (2) were unclassified ANA-positive. 88% (37) of patients had a positive ANA. HLA-B27 was positive in 6 patients. Of the 42 patients, 14 were treated with Etanercept (ETN), with remission achieved in 7 (50%). 3 patients were treated with infliximab, with remission only achieved for up to 18-24 months. Of the 33 patients treated with Adalimumab, only 4 failed to achieve remission. Of the 4 patients with Abatacept, 3 remain in treatment. Two patients treated with tocilizumab have less than 3 months of treatment. 27 patients only required one biological agent, a second biological agent was required in 11 patients and 3 or more biologicals were required in 4 patients. Treatment was suspended due to remission in 9 patients. 2 of these had a confirmed new exacerbation in the 3 first months after discontinuing treatment. Conclusions: Our results coincide with the results provided in the literature in that Adalimumab is highly effective in our patient group with uveitis and that Etanercept achieved remission in 50% of patients. Consider both abatacept and tocilizumab as treatment alternatives for patients who are refractory to anti-TNF therapy. Disclosure of Interest: None Declared